Probing molecular influence on photoemission delays - Biswas, Shubhadeep; Förg, B.; Schötz, J.; Schweinberger, W.; Ortmann, L.; Zimmermann, T.; Pi, L. W.; Baykusheva, D.; Masood, H. A.; Liontos, I.; Kamal, A. M.; Kling, N. G.; et al. (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
The advancement of attosecond chronoscopy has made it possible to reveal ultrashort time dynamics of photoionization [1]. Ionization delay measurements in atomic targets provide a wealth of information about the timing of the photoelectric effect [2], resonances, electron correlations and transport. The extension of this approach to molecules, however, presents great challenges. In addition to the difficulty of identifying correct ionization channels, it is hard to disentangle the role of the anisotropic molecular landscape from the delays inherent to the excitation process itself. Here, we present the measurements of ionization delays from ethyl iodide around the 4d giant dipole resonance of iodine. We employ attosecond streaking spectroscopy, which enables to disentangle the contribution to the delay from the functional ethyl group, being responsible for the characteristic chemical reactivity of the molecule. An attosecond extreme ultraviolet (XUV) pulse ionizes the molecule around the energy of the giant resonance and the released electron is exposed to the ponderomotive force of a synchronized near-infrared (NIR) field, which yields a streaking spectrogram (see figure). Comparative phase analysis of the spectrograms corresponding to iodine 4d and neon 2p emission permits extracting overall photoemission delays for ethyl iodide. The data is recorded for multiple photon energies around the iodine 4d resonance and compared to classical Wigner propagation [3] and quantum scattering [4] calculations. Here the outgoing electron, produced via inner shell ionization of the iodine atom in ethyl iodide, and thereby hardly influenced by the molecular potential during the birth process, acquires the necessary information about the influence of the functional ethyl group during its propagation. We find significant delay contributions that can distinguish between different functional groups, providing a sensitive probe of the local molecular environment [5]. This would stimulate to perform further angle resolved measurements in molecules to probe the potential landscape in three dimension.
CRIS-Team Scopus Importer:2023-04-20